ERAS protocol in colorectal surgery is effective in octogenarians: A retrospective cohort study - Justin Dourado, MD; Ariel Wolf, MD; Maria Herrera Rodriguez, DO; Shruti Agarwal, BS; Karin Blumofe, MD; Jordan Moseson, DO; Jose Yeguez, MD; Andrew Ross, MD; Avraham Belizon, MD (Surgery Open Science)
Purpose: Evaluate the effectiveness of implementing an ERAS protocol in octogenarians. Methods: This retrospective cohort study analyzed patients undergoing colorectal surgery under the ERAS protocol at Boca Raton Regional Hospital from December 1, 2019 to October 30, 2021. Patients under the age of 18, undergoing emergency surgery, and with incomplete data were excluded. A p < 0.05 was considered statistically significant and analyses were done using EZR and R software. Results: 299 patients met inclusion criteria with 60 (20.1 %) over the age of 80 and 239 (79.9 %) younger than 80. 140 (46.8 %) of the cohort were male. When comparing octogenarians with younger patients there were no differences in compliance with ERAS protocols such as pre-operative medication (p = 1) and oral carbohydrate drink consumption (p = 0.574), oral intake in PACU (p = 0.832), PACU sit and dangle (p = 0.619), or adherence to a narcotic sparing regimen (p = 0.365). Additionally, there were no differences in complications (p = 1), time until bowel function (p = 0.401), or time to first ambulation (p = 0.883). Octogenarians were more likely to have a longer LOS (4.89 v 3.0 days; p = 0.006), disposition requiring either home health care or a skilled nursing facility (SNF) (52.5 % v 28.3 %; p = 0.008), and readmission (42.3 % v 20.8 %; p = 0.042). Conclusion: The ERAS protocol is safe and effective when used in the octogenarian without decreased compliance or increased complications. Increased LOS, care needed on disposition, and readmission are in-line with other published data of all patients and are likely related to increased frailty among this group and not to the addition of the ERAS protocol.